Comparing Drone and Vessel‐Based Imaging to Quantify Epibiont Coverage on Humpback Whales - Isabel A. R. Taylor; Ticiana Fettermann; Barry McGovern; David S. Schoeman; Adrian B. McCallum; Stephanie H. Stack (Marine Mammal Science, 2026)
Cetacean epibionts offer noninvasive insights into host health, physiology, and spatial ecology, yet quantitative assessments in wild populations remain scarce. Although vessel‐based observations may be limited by field of view and analyst input, unoccupied aerial vehicles (UAVs; drones) are increasingly used to monitor cetacean health indices, enhancing observational availability and reproducibility. However, the suitability of drones for quantifying epibiota has not been thoroughly evaluated. Implementing a standardized workflow, we compared dorsal proportional epibiont coverage estimates derived from drone‐based imagery and traditional vessel‐based techniques across reproductive classes of humpback whales ( Megaptera novaeangliae ). We analyzed 32 paired datasets using pixel‐based methods, incorporating semiautomated graph‐cut segmentation and iterative color‐thresholding. Drone‐derived estimates of epibiont coverage consistently exceeded vessel‐based measures, which averaged 58% of the relative coverage estimated from corresponding drone imagery, partly attributable to variable lighting during image capture. Nevertheless, 94% of paired observations differed by less than 5% in absolute coverage, indicating strong agreement. While refinement of flight parameters, image resolution, and further validation are recommended, we demonstrate that drones can provide a reliable source of quantitative epibiont data, with potential applicability across diverse epibiont–host systems, benefiting cetacean population health monitoring programs and informing conservation strategies, particularly for elusive or understudied species.

Multinational evaluation of genetic diversity indicators for the Kunming‐Montreal Global Biodiversity Framework - Alicia Mastretta‐Yanes; Jessica M. da Silva; Catherine E. Grueber; Luis Castillo‐Reina; Viktoria Köppä; Brenna R. Forester; W. Chris Funk; Myriam Heuertz; Fumiko Ishihama; Rebecca Jordan; Joachim Mergeay; Ivan Paz‐Vinas; et al. (Ecology Letters, 2024)
Under the recently adopted Kunming‐Montreal Global Biodiversity Framework, 196 Parties committed to reporting the status of genetic diversity for all species. To facilitate reporting, three genetic diversity indicators were developed, two of which focus on processes contributing to genetic diversity conservation: maintaining genetically distinct populations and ensuring populations are large enough to maintain genetic diversity. The major advantage of these indicators is that they can be estimated with or without DNA‐based data. However, demonstrating their feasibility requires addressing the methodological challenges of using data gathered from diverse sources, across diverse taxonomic groups, and for countries of varying socio‐economic status and biodiversity levels. Here, we assess the genetic indicators for 919 taxa, representing 5271 populations across nine countries, including megadiverse countries and developing economies. Eighty‐three percent of the taxa assessed had data available to calculate at least one indicator. Our results show that although the majority of species maintain most populations, 58% of species have populations too small to maintain genetic diversity. Moreover, genetic indicator values suggest that IUCN Red List status and other initiatives fail to assess genetic status, highlighting the critical importance of genetic indicators.